Key ideas in educational research - Scott, David (Continuum, 2007)
It is easy for newcomers to educational research to be confused by the wide range of terms used in the field and consequently for them to find it challenging to relate such terms to their own research and practice. This comprehensive guide consists of 120 concise but illuminative essays providing: - an explanation and definition of the term - alternative explanations and definitions of the term - the context in which it is used by educational researchers - exemplars as to how the term is used and used be used in practice - references to further literature - cross-references to other terms in the book.